Promoting functional foods as acceptable alternatives to doping: potential for information-based social marketing approach - Petróczi Andrea; Naughton Declan P; James Ricky (Taylor & Francis Group, 2010)
Abstract Background Substances with performance enhancing properties appear on a continuum, ranging from prohibited performance enhancing drugs (PED) through dietary supplements to functional foods (FF). Anti-doping messages designed to dissuade athletes from using PEDs have been typically based on moralising sport competition and/or employing scare campaigns with focus on the negative consequences. Campaigns offering comparable and acceptable alternatives are nonexistent, nor are athletes helped in finding these for themselves. It is timely that social marketing strategies for anti-doping prevention and intervention incorporate media messages that complement the existing approaches by promoting comparable and acceptable alternatives to doping. To facilitate this process, the aim of this study was to ascertain whether a single exposure knowledge-based information intervention led to increased knowledge and subsequently result in changes in beliefs and automatic associations regarding performance enhancements. Methods In a repeated measure design, 115 male recreational gym users were recruited and provided with a brief information pamphlet on nitrite/nitrate and erythropoietin as a comparison. Measures of knowledge, beliefs and automatic associations were taken before and after the intervention with at least 24 hours between the two assessments. The psychological tests included explicit measures of beliefs and cognitive attitudes toward FF and PED using a self-reported questionnaire and computerised assessments of automatic associations using the modified and shortened version of the Implicit Association Test. Results The information based intervention significantly increased knowledge (p < 0.001), changed explicit beliefs in specific FF (p < 0.001) and shifted the automatic association of FF with health to performance (p < 0.001). Explicitly expressed beliefs and automatic associations appear to be independent. Conclusion Evidence was found that even a single exposure to a persuasive positive message can lead to belief change and can create new or alter existing associations - but only in the specific domain. Interventions to change outcome expectations in a positive way could be a rewarding avenue for anti-doping. Effective social marketing campaigns for drug free sport should follow appropriate market segmentation and use targeted messages via promoting the natural form as opposed to the purified form of the main active ingredient.